Neoadjuvant chemotherapy and radiotherapy outcomes in borderline‐resectable and locally‐advanced pancreatic cancer patients. (7th December 2022) - Botta, Gregory P.; Huynh, Tridu R.; Spierling‐Bagsic, Samantha R.; Agelidis, Alexander; Schaffer, Randolph; Lin, Ray; Sigal, Darren
Abstract: Background: There is no agreed upon standard of care for borderline‐resectable pancreatic cancer (BRPC) or locally‐advanced pancreatic cancer (LAPC) patients regarding the benefit of chemotherapy or radiation alone or in combination. Patients and Methods: We completed a retrospective cohort analysis of BRPC and LAPC patients at a cancer center with expertise in multi‐disciplinary pancreatic ductal adenocarcinoma (PDAC) treatment over a 5‐year period from 03/01/2014 to 03/01/2019 (cut‐off date). The total evaluable newly diagnosed, treatment naïve, BRPC, and LAPC patients with adequate organ function and ability to obtain treatment after multidisciplinary review was 52 patients. After analysis, patients were evaluated for rates of resection, extent of resection (R0 or R1), median progression‐free survival (mPFS), and median overall survival (mOS). Results: Patients were treated with chemotherapy alone (gemcitabine and nab‐paclitaxel = 77% (20/26); FOLFIRINOX = 19% (5/26); single agent gemcitabine 3.8% (1/26)), or chemotherapy followed by chemoradiation (gemcitabine +5 Gy × 5 weeks), or chemoradiation alone prior to re‐staging and potential resection. Of the 29% (15/52) of patients who went on to surgical resection, 73% (11/15) achieved R0 resection. An R0 resection was achieved in 35% (9/26) of patients treated with chemotherapy alone, 7.6% (1/13) in a patient treated with chemotherapy followed by radiation, and 7.6% (1/13) with concurrent chemoradiotherapy alone. Chemotherapy alone achieved a mPFS of 16.4 months ( p < 0.0025) and mOS of 26.2 months ( p < 0.0001), chemotherapy followed by chemoradiation was 13.0 months and 14.9 months respectively, while concurrent chemoradiotherapy was 6.9 months and 7.3 months. Conclusions and Relevance: BRPC and LAPC patients capable of surgery after only receiving neoadjuvant treatment with chemotherapy had higher rates of R0 resection with prolonged median PFS and OS compared with any patient needing combination chemotherapy with radiotherapy. Abstract : BRPC and LAPC patients capable of surgery after only receiving neoadjuvant treatment with chemotherapy had higher rates of R0 resection with prolonged median PFS and OS compared to any patient needing combination chemotherapy with radiotherapy.